Eksistensi Kesenian Ronggeng di Nagari Simpang Kecamatan Simpang Alahan Mati Kabupaten Pasaman - Erika Andela Br Sitepu (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2020)
Abstrak: Ronggeng is usually known as a traditional art that only develops in Java, in fact this art is also found in the Simpang community, Simpang Alahan Mati District of West Pasaman Regency in West Sumatra. Here, Ronggeng is performed at a wedding ceremony combined with Minangkabau customs, even the residents claim this art is an art that is in demand by the Nagari Simpang community. In this regard, researcher is interested in studying what causes the Ronggeng exists in Nagari Simpang, which is much influenced by Minangkabau culture. The purpose of this research is to describe the social practice of Ronggeng art in the Simpang community, the enabling structure for the existence of Ronggeng art and to see the role of the agency in this art performance. For that, structuration theory and qualitative research using observation and in-depth interviews were used. The results of this study indicate that Ronggeng is performed in Minangkabau traditional ceremonies, such as parties, circumcision of the apostle and batagak rumah (establishing a new house), including in events commemorating 17 August. This art is accepted in the local community because it is understood by local and their leaders as being in accordance with Minangkabau traditional values.